MANAGEMENT AND TRUST WORKERS - Nava Guibert, Luis (2019)
This article is aimed at law students who, as future lawyers, must be permanently updated on the concepts; therefore, in this opportunity I will develop the legal aspects of the right of management and trust workers to receive compensation for withdrawal of trust, which in the end we are faced with an arbitrary or uncaused dismissal, criteria that have varied throughout of the time between its granting or not.